Diversity and Distribution of Bracket Fungi in Mt. Kilakiron, Bukidnon, Philippines - Cababan, Mc Arthur Lequin; Jaranilla, Aprille Kake Ora; Bastatas, Mariane Catayas; Salvane, Chazzel Feel Comonong; Toldo, Uzziel Campuso (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2021)
Fungi have a lot of important function in the bionetwork resembling to decomposition and even nutrient cycling with respect to its symbiotic relationships with trees and other plants. This study aimed to assess the diversity and distribution of bracket fungi in Mt. Kilakiron, Portulin, Pangantucan, Bukidnon. Thus, floristic survey was conducted in one of the mountain of Mindanao to provide information as to what and how many species of bracket fungi are present in Mt. Kilakioron, Bukidnon, Philippines. Â 40 total species belonging to 17 genera and 5 family was collected and assessed. 12 individuals of Trametes versicolor were observe which favors dwellings with low temperature and high altitude are. Additionally, study revealed that most types of bracket fungi initiate in the site are decomposers and saprophytic in nature which contributes a lot in the process of putrefaction. The species of bracket fungi in Mt. Kilakiron clearly shows abundant and provides a large contribution to the ecosystem having high Shannon diversity index. The significance of each environmental factor is discussed in relationship to the ecology of the species. Bracket fungi are reliant on the climatic and conservational settings which makes them as excellent natural pointers of ecosystem in the forests of Mindanao Island, Philippines.